Analysis Of The Impact Of Covid-19 On The Income Of Oil Palm Farmers In Kuantan Singingi Regency - Alatas, Andi; WM Vermila, Chezy; Jamalludin, Jamalludin (International Journal of Educational Research & Social Sciences, 2022)
With the title Analysis of the Impact of Covid-19 on the Income of Oil Palm Farmers in Kuantan Singingi Regency. The purpose of this study was to find out how the impact of covid-19 on the income of oil palm farmers in Kuantan Singingi Regency. The analytical method used is mathematical analysis and descriptive analysis by simplifying table data. The data collected in this study are primary and secondary data. Primary data obtained through interviews with respondents using questionnaires. The results showed that there was a significant difference in palm oil production before and during the COVID-19 pandemic and there was a significant difference in farmers' income before the pandemic, which was Rp. 13,795,936 and during the pandemic, which was Rp. 11,175,474.